2018
DOI: 10.17650/2313-805x-2018-5-1-26-34
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous replication in oncological patients

Abstract: Эпигенетика-наука об обратимых наследственных изменениях функционирования гена, которые происходят без изменений в нуклеотидной последовательности ДНК. Один из важнейших маркеров нарушений эпигенетической регуляции генома клеткиасинхронность репликации ДНК биаллельно экспрессирующихся генов. Удобным методом оценки нарушения синхронности репликации (асинхронной репликации) в культивированных лимфоцитах периферической крови человека, как правило, является интерфазная флуоресцентная in situ гибридизация (I-FISH).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…Our study on lymphocytes with asynchronous replication of the TP53 gene both in cancer-free subjects and in patients with solid tumors showed good agreement with the main findings of others [8,24,27]. Thus, our results on the replication timing of biallelically expressed genes in blood lymphocytes from cancer patients [9,28], suggest that AGR can serve as a nonspecific marker of cancer.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study on lymphocytes with asynchronous replication of the TP53 gene both in cancer-free subjects and in patients with solid tumors showed good agreement with the main findings of others [8,24,27]. Thus, our results on the replication timing of biallelically expressed genes in blood lymphocytes from cancer patients [9,28], suggest that AGR can serve as a nonspecific marker of cancer.…”
Section: Discussionsupporting
confidence: 89%
“…In [8], the authors showed that in patients with renal cell carcinomas, the number of lymphocytes with AGR for the TP53 gene and locus 21q22 was 36 and 44%, respectively, while in healthy individuals, the numbers were much lower: 12 and 14%. Subsequently, such studies were carried out with other genes both in healthy controls and in cancer patients [9].…”
Section: Introductionmentioning
confidence: 99%